Engineering an Antibody V Gene-Selective Vaccine - Ronsard, Larance; Yousif, Ashraf S.; Peabody, Julianne; Okonkwo, Vintus; Devant, Pascal; Mogus, Alemu Tekewe; Barnes, Ralston M.; Rohrer, Daniel; Lonberg, Nils; Peabody, David; Chackerian, Bryce; Lingwood, Daniel (Frontiers in Immunology, 2021)
The ligand-binding surface of the B cell receptor (BCR) is formed by encoded and non-encoded antigen complementarity determining regions (CDRs). Genetically reproducible or ‘public’ antibodies can arise when the encoded CDRs play deterministic roles in antigen recognition, notably within human broadly neutralizing antibodies against HIV and influenza virus. We sought to exploit this by engineering virus-like-particle (VLP) vaccines that harbor multivalent affinity against gene-encoded moieties of the BCR antigen binding site. As proof of concept, we deployed a library of RNA bacteriophage VLPs displaying random peptides to identify a multivalent antigen that selectively triggered germline BCRs using the human VH gene IGVH1-2*02. This VLP selectively primed IGHV1-2*02 BCRs that were present within a highly diversified germline antibody repertoire within humanized mice. Our approach thus provides methodology to generate antigens that engage specific BCR configurations of interest, in the absence of structure-based information.